The Effect of Budgetary Participation, Organizational Commitment, and Leadership Styles on the Employees’ Performance - Mila Purani Sistiyan; Palikhatun Palikhatun; Payamta Payamta (SEISENSE Journal of Management, 2019)
Aim -This study aimed at gaining the empirical evidence vis-a-vis the effect of budgetary participation, organizational commitment, and leadership styles on the employees’ performance.